Linkage between Dust Cycle and European Loess in the Last Glacial Maximum Determined by Atmospheric Model Simulations - Schaffernicht, Erik Jan (2018)
The Last Glacial Maximum (LGM) is a turning point of the Earth’s climate and the human dispersal. Yet, the then prevailing atmosphere dynamics over Europe and the North Atlantic as well as the mineral dust cycle in Europe are not well understood. This dissertation improves understanding the LGM climate and its dust cycle. Based on global climate simulations, it compares the LGM climatologies, jet stream, Circulation Weather Types (CWTs), and Combined Empirical Orthogonal Functions (CEOFs) with their present analogues. The dust cycle was reconstructed for Europe based on statistic dynamic downscaling using CWT frequency-conform regional Weather Research and Forecasting Model (WRF) simulations for the LGM. Proxies and reanalyses served to evaluate all simulations; among them a comprehensive compilation of loess-based reconstructed mass accumulation rates for the LGM. By comparing the simulated LGM depositions with these rates,linkage was established between the LGM dust cycle and the present loess. For the North Atlantic and Europe, the CEOFs suggest a lower LGM than present climate variability. The jet stream was narrower and partly more than 10 m/s faster there. Possible subsequent jet stream paths ran over and along the Nordic Seas, eastwards along the onset of the Central German Uplands or over the Mediterranean. The North Atlantic Oscillation (NAO) was 50% stronger combined with a 6° wider (westward) Azores High. The latitude-deviating LGM temperatures indicate that the North Atlantic Current extended up to Norway. Precipitation reduced by more than 150 mm/yr over the proglacial European areas; including a reduction of more than 300 mm/yr over the North Sea Basin. Near the EIS coast, periods of precipitation and temperatures that ranged below their climatological average synchronized with above-average precipitation periods over the Azores; both likely correlating with a below-average NAO. Similarly, stronger EIS High periods correlated with reduced precipitation and temperatures in western and central ...